IN VITRO ANTI-INFLAMMATORY AND FREE RADICAL SCAVENGING ACTIVITIES OF CRUDE SAPONINS EXTRACTED FROM ALBUCA BRACTEATA JACQ. BULB. - Odeyemi, Samuel; Afolayan, Anthony; Bradley, Graeme (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Albuca bracteata is a medicinal plant traditionally used in the management of diabetes mellitus in the Eastern Cape of South Africa. The purpose of this study was to evaluate the antioxidant and anti-inflammatory activities of saponins extracted from the bulb of Albuca bracteata and compared with the crude methanolic extract. Methods: In vitro antioxidant activity was determined using free radical scavenging assays such as DPPH, ABTS and NO2. The anti-inflammatory potential was carried out using inhibition of protein denaturation of egg albumin as a model of anti-inflammatory capacity.Results: Both the crude methanolic extract and saponins showed inhibition of DPPH, ABTS and NO2 scavenging activity. However, the free radical scavenging activity of isolated saponin compared favourably with Rutin and BHT. The crude methanolic extract showed higher inhibition percentage of protein denaturation compared with the saponins at the concentration investigated. Conclusion: This study indicates that saponin from Albuca bracteata bulb possess potent anti-inflammatory activity and is also a good source of natural antioxidant.